Currents in defective coupled ratchets - Fendrik, Alejandro José (2012)
Transport phenomena in a one-dimensional system of interacting particles is studied. This system is embedded in a periodic and left-right asymmetric potential driven by a force periodic in time and space. When the density (number of particles per site) is an integer, directional current of the particles is collective; that is, it involves the whole system since all the sites are equivalents. On the other hand, when the system has a defect, a new localized or noncollective current appears due to the migration of defects from one site to another. We show here how this “defective” (defects generated) current can be controlled by white noise.